A carboxy-terminal monoleucine-based motif participates in the basolateral targeting of the Na+/I- symporter - Martín, Mariano (2019)
The Na+/iodide (I2) symporter (NIS), a glycoprotein expressed at the basolateral plasma membrane of thyroid follicular cells, mediates I2 accumulation for thyroid hormonogenesis and radioiodide therapy for differentiated thyroid carcinoma. However, differentiated thyroid tumors often exhibit lower I2 transport than normal thyroid tissue (or even undetectable I2 transport). Paradoxically, the majority of differentiated thyroid cancers show intracellular NIS expression, suggesting abnormal targeting to the plasma membrane. Therefore, a thorough understanding of the mechanisms that regulate NIS plasma membrane transport would have multiple implications for radioiodide therapy. In this study, we show that the intracellularly facing carboxy-terminus of NIS is required for the transport of the protein to the plasma membrane. Moreover, the carboxy-terminus contains dominant basolateral information. Using internal deletions and site-directed mutagenesis at the carboxy-terminus, we identified a highly conserved monoleucine-based sorting motif that determines NIS basolateral expression. Furthermore, in clathrin adaptor protein (AP)-1B-deficient cells, NIS sorting to the basolateral plasma membrane is compromised, causing the protein to also be expressed at the apical plasma membrane. Computer simulations suggest that the AP-1B subunit s1 recognizes the monoleucine-based sorting motif in NIS carboxy-terminus. Although the mechanisms by which NIS is intracellularly retained in thyroid cancer remain elusive, our findings may open up avenues for identifying molecular targets that can be used to treat radioiodide-refractory thyroid tumors that express NIS intracellularly.